Composite Sandwich Footbridge – Numerical ESL FEM Calculations vs. In Situ Measurements - MIŚKIEWICZ, Mikołaj; CHRÓŚCIELEWSKI, Jacek; SOBCZYK, Bartosz; PYRZOWSKI, Łukasz (Engineering Transactions, 2017)
Selected results of the static analysis of composite sandwich footbridge with the corresponding in situ measured values are compared in the paper. The analysed bridge is a research object, which was built in 2015 and is currently located at the Gdańsk University of Technology campus. Since it is a novel structure, a proper definition of the bridge numerical model, allowing its safe design, is very important. Therefore, instead of some preliminary research, carried out on sandwich beams or the bridge segment, also the calculated structural properties of the full scale object should match the experimentally predicted response. This verification was required to obtain permission for the bridge exploitation, according to the government regulations.